Temperature and velocity distributions from numerical simulations of ceiling jets under unconfined, inclined ceilings. (July 2017) - Chatterjee, Prateep; Meredith, Karl V.; Wang, Yi
Abstract: Numerical simulations of ceiling jets under unconfined, inclined ceilings were conducted with the open-source code FireFOAM. A range of ceiling inclinations, 0–30° was considered with a 14 kW convective heat release rate (HRR) heptane fire used as the plume source, and the ceiling mid-point clearance from the top of the 0.228 m diameter burner kept fixed at 0.89 m. The predicted temperature and velocity in the developing ceiling jets were compared against the experimental data and empirical correlations. Temperature and velocity predictions on the elevated side of the ceiling are in general agreement with experimental data. Flow reversal in the lower side of the ceiling was predicted with good confidence, and comparison with experimental data was found to be reasonable. Following existing convention in the literature, the predicted results were non-dimensionalized using the convective HRR, ceiling height and radial distance from the ceiling mid-point. Comparison of the non-dimensional data on the elevated ceiling side showed better agreement for temperature against the correlation, whereas predicted velocity data showed a wider spread around the correlation values.